Pneumococcal conjugate vaccine implementation in middle-income countries - Tricarico, Serena; McNeil, Hannah C.; Cleary, David W.; Head, Michael G.; Lim, Victor; Kok, Ivan Seng Yap; Chong, Chun Wie; Cheng, Siang Tan; Mohd Nor, Norazmi; Ismail, Aziah; Seong, Eddy Guan Cheah; Faust, Saul N.; et al. (BioMed Central, 2017)
Since 2000, the widespread adoption of pneumococcal conjugate vaccines (PCVs) has had a major impact in the prevention of pneumonia. Limited access to international financial support means some middle-income countries (MICs) are trailing in the widespread use of PCVs. We review the status of PCV implementation, and discuss any needs and gaps related to low levels of PCV implementation in MICs, with analysis of possible solutions to strengthen the PCV implementation process in MICs.